The Determinants of Commercial Bank Profitability in Sub-Saharan Africa - Flamini, Valentina (IMF Working Papers; Working Paper ;, 2009)
Bank profits are high in Sub-Saharan Africa (SSA) compared to other regions. This paper uses a sample of 389 banks in 41 SSA countries to study the determinants of bank profitability. We find that apart from credit risk, higher returns on assets are associated with larger bank size, activity diversification, and private ownership. Bank returns are affected by macroeconomic variables, suggesting that macroeconomic policies that promote low inflation and stable output growth does boost credit expansion. The results also indicate moderate persistence in profitability. Causation in the Granger sense from returns on assets to capital occurs with a considerable lag, implying that high returns are not immediately retained in the form of equity increases. Thus, the paper gives some support to a policy of imposing higher capital requirements in the region in order to strengthen financial stability.